An Analysis of Mechanical Errors in Writing Skill - Zulfatun Mahmudah (English LAnguage Study and TEaching, 2022)
Writing skill is one of the important language skills for students. The purpose of this study was to find out the kinds of mechanical errors produced by the 10th grade students at SMAN 11 Banda Aceh. The method used was descriptive quantitative research design. The population comprised 204 students at the 10th grade of SMAN 11 Banda Aceh, while the samples were 30, selected by using cluster random sampling. This study used test as an instrument for data collection. In analyzing the data, the researcher used two steps, namely identifying of mechanical errors and classifying them based on their types. The results showed that the students produced 582 errors in total, which were categorized into three types: errors of punctuation, errors of capitalization, and errors of spelling. In details, the students made 236 errors of punctuation (40, 54%), 312 errors of capitalization (53, 60%), and 34 errors of spelling (5, 84%). The most dominant type of mechanical errors made by students was the errors of capitalization.